LANDSCAPE PLANNING OF THE CULTURAL INTERPRETATION TRAIL OF THE MUARAJAMBI TEMPLE NATIONAL AREA WITH A SUSTAINABLE CULTURAL TOURISM APPROACH - Maharani, Fetty Jihan; Pratiwi, Rian Adetiya; Muljana, Martin (Lakar: Jurnal Arsitektur, 2024)
The National Cultural Heritage Area of Muarajambi Temple is one of the leading tourism destinations in Jambi Province. However, the lack of attention and contribution from the government in managing the historical and cultural tourism sector has caused the potential of this area in terms of destination, industry, and marketing in Muarajambi Regency are not optimal. These conditions mean that The National Cultural Heritage Area of Muarajambi Temple need to be developed through landscape planning with a sustainable cultural tourism concept approach. This research aims to identify the potential and constraints in the Muarajambi Temple National Heritage Area, and offer solutions for spatial planning through cultural landscape planning. To execute this plan, researchers used the design method by LaGro through the inventory stages to the use of a sustainable cultural tourism concept approach The development of this research planning was taken from the book of the Muarajambi National Cultural Heritage Area Management Master Plan compiled by the Directorate of Cultural Development and Utilization, Directorate General of Culture, & Ministry of Education, Culture, Research, & Technology as a source of regulatory reference. This book describes regulations related to the history, management, and form of planning for the KCBN area, which then in this study examines the factors that cause problems and the potential of the site, then formulates solutions in a landscape plan in a sustainable cultural tourism concept approach that has not been previously stated. The final results of the study are packaged in the form of a masterplan visualization, siteplan, and 3D visualization to realize the Muarajambi Temple National Cultural Heritage Area as a sustainable cultural tourism destination.